The Appropriate Pancasila Education Contents to Implant Lofty Values for Indonesian Students - Taniredja, Tukiran; Afandi, Muhammad; Faridli, Efi Miftah (EDUCARE, 2012)
ABSTRACT: âPancasilaâ (Five Basic Principles of the Republic of Indonesia) Education subject, which was before Reformation era (1998) known widely by Indonesian community, nowadays has undergone marginalization process in social, national, and state living. It is due to, one of the factors, that âPancasilaâ Education subject has been made as indoctrination means and authority political needs in performing development in the New Order government era (1966-1998). Although âPancasilaâ Education subject has not been exit in educational curriculum in Indonesia since 2003, but now it is realized the need of developing awareness about âPancasilaâ lofty values toward college students as the candidate of next national leader. Of the appropriate âPancasilaâ Education subject contents to implant lofty values toward Indonesian students, the study finding shows that the respondents agreed with re-emphasizingÂ  the matters related to: (1) the foundation and aim of âPancasilaâ Education; (2) âPancasilaâ in historical context of Indonesian struggle; (3) âPancasilaâ as philosophical system; (4) âPancasilaâ as political ethic; (5) âPancasilaâ as national ideology; (6) âPancasilaâ in state administration of Indonesian Republic; and (7) âPancasilaâ as social, national, and state living paradigm in Indonesia to be developed continuously in Indonesian community. KEY WORDS: âPancasilaâ education subject, lofty values, Indonesian college students, globalization process, and national character and identity.Â Â Â Â Â About the Authors: Prof. Dr. Haji Tukiran Taniredja, Muhammad Afandi, M.Pd. and Efi Miftah Faridli, M.Pd. are the Lecturers at the Faculty of Education and Teacher Training UMP (Muhammadiyah University of Purwokerto), Jalan Raya Dukuhwaluh P.O. BOX 202, Purwokerto 53182, Central Java, Indonesia. Phone: +62281 636751. E-mails: tukiranump@yahoo.com and efimiftahfaridli@yahoo.co.idHow to cite this article? Taniredja, Tukiran, Muhammad Afandi & Efi Miftah Faridli. (2012). âThe Appropriate Pancasila Education Contents to Implant Lofty Values for Indonesian Studentsâ in EDUCARE: International Journal for Educational Studies, Vol.5(1) August, pp.107-116. Bandung, Indonesia: Minda Masagi Press owned by ASPENSI in Bandung, West Java; and FKIP UMP in Purwokerto, Central Java, ISSN 1979-7877.Chronicle of the article: Accepted (June 27, 2012); Revised (July 30, 2012); and Published (August 17, 2012).